(untitled) (Medico Legal Update, 2020)
Background: Low- and high- oncogenic risk human papilloma viral infections have been related to the genesis of a variety of human benign and malignant tumors in the oral cavity and nasopharyngeal tissues. High- risk types of human papilloma virus are now well established as major etiologic factors of head and neck cancers, including tonsillar carcinomas. Objective: The current prospective case- control study aimed to unravel the frequency of HPV genotype 16/18 DNA detection rates in the adenoctomized tissues from patients with nasopharyngeal tonsillar adenoid hypertrophy. Materials and Method: A sixty (60) nasal as well as nasopharyngeal adenotonsillar tissues obtained from patients with adenoid hypertrophy via adenoctomies were enrolled. Forty (40) adenotonsillar tissues were from patients with adenoid hypertrophy, and (20) normal nasal tissue specimens were obtained from pediatric patients following trimming operations of inferior nasal turbinates’ with unremarkable pathological changes (as an apparently healthy control group). A recent version of chromogenic in situ hybridization (CISH) method for HPV detection were performed by using specified DNA probes for DNA of high- risk HPV 16/18 genotypes. Results: Among nasopharyngeal adenotonsillar tissues group, 15 out of 40 have revealed positive CISH signals for DNA of HPV 16 / 18 genotype, constituting 35% of the total screened adenoid hypertrophied tissues. No positive– CISH reactions were detected in the control nasal tissues. Statistically, the results obtained in this study showed significant difference when compared to the control tissues group. Conclusions: The significant rate of such high- oncogenic HPV genotypes detection in those nasopharyngeal adenotonsillar tissues criticizes searching its further importance, as HPV 16/18 genotypes are critically correlated to many pre- neoplastic as well as malignant lesions.